Utilization of Artificial Intelligence in Automating the Writing of News Texts in High School: Chatgpt Case Study - Fidyatun Hasanah; Irma Suryani; Warni (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Abstract Advances in artificial intelligence (AI) technology have opened up new opportunities in various fields, one of which is journalism. In the rapidly developing digital era, the use of AI in the media production process, including news writing, is becoming increasingly relevant. This research aims to analyze the use of ChatGPT, an AI-based language model, in automating news text writing. This model is capable of processing and generating text automatically, which can speed up and simplify journalists' tasks in producing news content. The method used in this research is a case study with a qualitative descriptive approach to explore more deeply the role and contribution of ChatGPT in news writing. The research results show that ChatGPT can help increase speed and efficiency in the news writing process. This model can organize news structures systematically, provide editing suggestions, and produce text with a neater flow. However, there are several challenges that need to be considered, such as the accuracy of the information produced, potential algorithm bias, and limitations in understanding more complex contexts. ChatGPT, although advanced, still has limitations in dealing with issues that require in-depth reasoning or richer substantive interpretation. The implications of this research provide broader insight into the potential and limitations of using AI to support modern journalism practices, as well as opening further discussions regarding ethics and responsibility in the use of this technology. Apart from that, the results of this research can also be used in learning to write news in high school to improve students' skills in understanding effective journalistic structure and language.